(untitled) (American Journal of Management, 2016)
While conducting empirical research regarding the relationship between case characteristics and student performance, the authors were surprised to find a lack of conceptual and empirical research regarding instructor case selection. This conceptual paper explores the case selection process and introduces case selection as an under-investigated component of the case teaching method in management education. Case selection is important because it is a critical component of the case teaching method. There has been no empirical testing of the effectiveness of case selection technique. The authors identify and propose case selection criteria for instructors of management education.